Pharmaceutical Product Withdrawal Periods in Mongolia: Current Situation and Efforts to Improve Knowledge and Practices - Gibson, Stephan (My University, 2013)
Mongolia is a nation with a long and rich history of herding livestock as the main source of food. Since independence from the Soviet Union in 1990, it has undergone many adjustments in the livestock industry including the introduction of many new drugs for livestock during a period of transition to a free-market economy, which has made it difficult to make and enforce regulations on things such as withdrawal periods. The issue of withdrawal periods and drug residues is attracting more attention, especially as the industry seeks to gain access to foreign markets. V.E.T. Net NGO Mongolia is an organization of American and Mongolian veterinarians working to further the education of veterinarians and livestock herders in Mongolia on various aspects of animal husbandry. V.E.T. Net provided the opportunity to conduct a survey of herders and veterinarians to assess current knowledge, attitudes, and practices regarding withdrawal periods. Additionally, training materials for veterinarians and herders were prepared for use by V.E.T. Net to promote adherence to withdrawal periods. This field experience report sets the stage by looking at the current situation of livestock herding, veterinary medicine, meat and milk supply, and drug residue regulations and testing in Mongolia, followed the results and interpretation of the herder and veterinarian surveys conducted. Finally, the recommended direction of subsequent work regarding withdrawal periods in Mongolia is discussed.
Keywords: Mongolia; Public Health; Pharmaceutical withdrawal periods; Public Health (0573)